Computational quantum chemistry II : the group theory calculator - Quinn, Charles M. (Academic Press, 2005)
Modern Computational Quantum Chemistry is indispensable for research in the chemical sciences. Computational Quantum Chemistry II - The Group Theory Calculator describes the group theory that the authors have developed in the past twenty-five years and illustrates how this approach, known as the 'Spherical Shell' method, can be applied to solve a variety of problems that benefit from a group theory analysis. To complement the theory, the book is supplied with a CD-ROM (Windows & trade; application), on which interactive files, based on EXCEL spreadsheet technology controlled by Visual Basic code, can be used to perform straightforwardly group-theory analyses for direct application to the simplification of physical problems in Chemistry, Physics and even Engineering Science. The Group Theory Calculator Web page is located at http://www.chemistry.nuim.ie/gt_calculator.htm. The primary purpose of this Web page is to identify and resolve any problems encountered while using the MS EXCEL files on the CD-ROM (included with the book). The Web page is maintained by Charles M. Quinn and allows readers to gain updates and news relating to this publication. * A comprehensive description of the authors' revolutionary group theory and structural chemistry methodology * A unique reference/ teaching work together with a CD-ROM filled with powerful interactive files that can be applied to solve group theory problems * Valuable companion for instructors, designers and students * Contains powerful calculators that are simple to use and do not require detailed knowledge for their application.